2007
DOI: 10.1007/bf03062308
|View full text |Cite
|
Sign up to set email alerts
|

Curves of expected recovery and their predictive validity for identifying treatment failure

Abstract: De auteurs van dit artikel presenteren 'verwacht-herstelgrafieken' (expected recovery curves) als maatstaf om de voortgang respectievelijk achteruitgang tijdens een psychotherapeutische behandeling van jongeren te 'monitoren'. Kinderen (of hun ouders) en adolescenten die in psychotherapie waren, vulden daartoe regelmatig de Youth outcome questionnaire-30 (YOG-30) in. De scores van alle patie¨nten werden samengenomen in een dataset, waaruit grafieken voor het te verwachten herstel werden afgeleid, uitgaande van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Psychotherapy research suggests that 5-10% of adult psychotherapy clients can be classified as experiencing deterioration or treatment failure-leaving treatment significantly worse off than when they entered (Lambert and Bergin 1994;Mohr 1995). Similar estimates of deterioration have been found for child and adolescent populations in managed care settings (Bishop et al 2005;Bybee et al 2007), and rates may be even higher for children and adolescents in traditional community mental health settings (Weisz et al 1995). In a related vein, Lilienfeld (2007) asserted that greater emphasis should be placed on research identifying potentially harmful treatments than on identifying empiricallysupported therapies.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Psychotherapy research suggests that 5-10% of adult psychotherapy clients can be classified as experiencing deterioration or treatment failure-leaving treatment significantly worse off than when they entered (Lambert and Bergin 1994;Mohr 1995). Similar estimates of deterioration have been found for child and adolescent populations in managed care settings (Bishop et al 2005;Bybee et al 2007), and rates may be even higher for children and adolescents in traditional community mental health settings (Weisz et al 1995). In a related vein, Lilienfeld (2007) asserted that greater emphasis should be placed on research identifying potentially harmful treatments than on identifying empiricallysupported therapies.…”
Section: Introductionmentioning
confidence: 70%
“…Utilizing empirically-derived change trajectories based on multilevel modeling (MLM), Bybee et al (2007) tested the accuracy of a similar warning system using a large archival database of children and adolescents served in a managed care setting. In this study, the warning system accurately identified 72% of youth patients who ultimately ended treatment with a negative outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We used cutoff scores at each measurement occasion to identify at-risk cases (c.f. Bybee et al, 2007;Cannon, Warren, Nelson, & Burlingame, 2010;Finch et al, 2001). We intended these cutoffs to identify the most extreme portion of scores that were worse than expected, on any measurement occasion.…”
Section: Analysesmentioning
confidence: 97%
“…For example, Lambert, Whipple, Bishop et al (2002) reported overall hit rates with adult patients of .79 and .83 for rationally derived and empirically derived methods, respectively. Similarly, Bishop et al (2005) reported an overall hit rate of .81 for a combined sample of youth served in residential and outpatient settings, and Bybee et al (2007) achieved an overall hit rate of .88 for youth in outpatient managed care settings. Relative to these studies, the overall hit rate for the present study (.75) may be a conservative estimate due to the methodology we employed for including scores that could be used as an alert signal.…”
mentioning
confidence: 90%
See 1 more Smart Citation